Agribisnis Tanaman Hortikultura di Kabupaten Cilacap Provinsi Jawa Tengah - Mais Ilsan; Agus Dwi Nugroho; Efrinda Efrinda; Winaryo Winaryo; Reineta Puspitasari; Rini Handoyo; Suparmono Suparmono (Agro Ekonomi, 2016)
The contribution of agriculture in the Cilacap’s GDP has continued decline but agricultural labor is still quite large. It has implications for the future, especially for the welfare of agricultural labor will be decrease. The purpose of this study was to determine the competitive commodities for horticulture in Cilacap and feasibility of investment and development strategy of the competitive commodities. This research was conducted in June-August 2016. The data used is primary data through observations and interviews and secondary data obtained from the relevant agencies. Analysis of data using Location Quotient (LQ), Rasmussen's Dual Criterion (RDC), investment feasibility, land suitability and SWOT. Commodity that have a lucrative opportunity in Cilacap for horticultural crops include chilli, mangosteen and banana. In order to develop agribusiness in Cilacap, improving the quality of human resources in agriculture as well as group activities; increase promotional efforts for competitive commodities will require the provision of information competitive commodities for investors; extending the land, control over land use, guaranteed prices for competitive commodities, climate change mitigation, infrastructure development and ease access to credit for farmers; and more study for each commodity